Impact of Teaching on Teacher - Students Relationship at Secondary Level in Bangladesh - Khaleduzzaman, Dr. Md. (Social Science Learning Education Journal, 2017)
The study explores the affective domain of teacher student relationships. Here produced a synthesis of information that guides a classroom teacher in the development and maintenance of teacher relationships with their students. The resulting analysis and interpretation provided a description of major themes that developed regarding strong teacher student relationships, as well as, specific components to the interactions considered essential for the studentâs learning environment. The outcome of this study is an account of experiences and procedures that guide the development and maintenance of relationships between a teacher and the students. Based on the findings, of the study represent an interpersonal framework for the learning environment. Conducting this study was to provide more specific examples of and empirical findings for how teacher student relationships are created. Identifying specific factors associated with teacher student interactions could provide valuable information to an educational learning community. Implications for how these findings can impact the learning environment at secondary level in Bangladesh]